VERBAL AND NON-VERBAL IN GREY'S ANATOMY SERIES "PAPA DON'T PREACH" : AN ETHICAL COMMUNICATION IN ABORTION - Rita Hartati,; Afifah Putri Eryani, (Journal of Innovation Research and Knowledge, 2023)
In Season 16 episode 7 'Papa Don’t Preach', is told about a patient named Cassidy Gardner who is 25 years old. Cassidy fell down the stairs, and upon checking the doctor found that the patient was pregnant. Before falling from the stairs it turns out she was trying to abort her womb. Cassidy asked the doctors to abort her pregnancy and got two different responses from the two doctors. From the explanation, it can be seen that this film is interesting for researchers because researchers want to see whether the verbal and non-verbal communication made between the two doctors who treat patients fulfill the Hippocratic Oath. The researcher wants to know the verbal and non-verbal communication of actors who took the Hippocratic Oath and the Oath, and what verbal and non-verbal communication violates the Hippocratic Oath. This study uses a descriptive qualitative method. The researcher separates the verbal and non-verbal data obtained from the film, then categorizes them according to the fulfilled and violated Hippocratic oaths. And from this research, it was found that the total verbal communication was ethically appropriate and absent by 59% and non-verbal ethically appropriate and absent by 41%.